Pengaruh Program Pemberdayaan Remaja Cerdas Terhadap Pengetahuan Dan Sikap Seks Pranikah Berisiko - Gumelar, Wahyu Retno; Ekawati, Heny; Setiawan, Dewa Galuh (Jurnal Keperawatan Muhammadiyah, 2025)
Risky premarital sexual behavior has become a growing concern for both the public and governmental institutions. Such behavior is associated with various negative outcomes, including the transmission of sexually transmitted infections (STIs), teenage pregnancy, and other health-related consequences. This study aims to analyze the effect of Smart Youth Empowerment Program on adolescents’ knowledge and attitudes toward risky premarital sexual behavior at Bojonegoro Regency. A pre-experimental design employing a one-group pre-test and post-test approach was used. The study population comprised 253 students, from which 80 respondents were selected using simple random sampling with an additional 10% adjustment. Data were collected using a questionnaire that assessed participants' knowledge and attitudes toward risky premarital sexual behavior. The data were tabulated and analyzed using the Wilcoxon Signed Rank Test with a significance level of p < 0.05. The findings revealed that prior to the intervention, a majority of students (78.8%) had low levels of knowledge, and nearly two-thirds (67.5%) demonstrated negative attitudes. Post-intervention, 92.5% of students displayed high knowledge levels, and all participants (100.0%) exhibited positive attitudes.The Wilcoxon test showed a significant result (p = 0.000), indicating that the intervention significantly influenced students’ knowledge and attitudes regarding risky premarital sexual behavior. Thus, Smart Youth Empowerment Program serves as a promising strategy for improving adolescent awareness and promoting healthier attitudes in the context of sexual health education.